Máquina lingüística. Una lectura del problema del lenguaje en la filosofía temprana de Giorgio Agamben - Fleisner, Paula (2012)
In Il linguaggio e la morte, Giorgio Agamben aims to dismantle the mythologem that reveals the essential negativity attributed to the ´human´: the Western assumption of an unbreakable and fundamental link between the human faculties of Language and Death. This metaphysical problem is thought as an ethical problem: the Voice is the negative foundation, the usual abode -always divided- of man. If many years later, in L´aperto, Agamben can explicitly pose the need for a genealogy of ´Life´ and review the operation of the ´anthropological machine´ that makes 'men' from the cuts established in the 'Living', is partly because twenty years earlier he had raised the issue of the relationship man/animal from the point of view of language. This article proposes an analysis of this 'language machine' that produces the ´Human´ from phoné/logos excision, which operation Il linguaggio e la morte demonstrates. Such a Metaphysics overcoming as proposed in this book implies not only a critique of the ´subject´ of knowledge but also a new look on how it was built in the West this device we call ´man´, i.e. an analysis of the humanization process that occurs in language and through contact with death. This paper elaborates an interpretation on agambenian conception of language as formulated in this seminar, taking into account the previous and later considerations, in order to clarify its contribution to contemporary criticism of the concept of ´man´.